(untitled) (Politeja, 2020)
Why Am I Still Thinking about World War II? Post-memory Experience of Sacha Batthyany Sacha Batthyany found out that in 1945 his aunt hosted a ball during which 180 Jews were shot by her guests. Their mass grave has not been found until today. She also helped many Nazis escape from Hungary. Sacha’s family kept these stories secret for years. For Sacha, the discovery of his family’s past becomes the beginning of a new life, recognizing the tormenting feeling of guilt as inherited from his ancestors. Can we define the sense of guilt as traumatic? We can certainly try to do it. Yet, trauma assumes different shapes and reveals its huge interpretative potential.